K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(\frac{2}{3}.\frac{4}{5}+\frac{1}{3}.\frac{4}{5}=\frac{4}{5}\left(\frac{2}{3}+\frac{1}{3}\right)=\frac{4}{5}.\frac{3}{3}=\frac{4}{5}.1=\frac{4}{5}\)

\(\frac{1}{2}:\frac{3}{4}+\frac{1}{6}:\frac{3}{4}=\frac{3}{4}:\left(\frac{1}{2}+\frac{1}{6}\right)=\frac{3}{4}:\frac{2}{3}=\frac{9}{8}\)

\(\frac{2}{3}.\frac{4}{5}-\frac{1}{3}.\frac{4}{5}=\frac{4}{5}\left(\frac{2}{3}-\frac{1}{3}\right)=\frac{4}{5}.\frac{1}{3}=\frac{4}{15}\)

\(\frac{1}{2}:\frac{3}{4}-\frac{1}{6}:\frac{3}{4}=\frac{3}{4}:\left(\frac{1}{2}-\frac{1}{6}\right)=\frac{3}{4}:\frac{1}{3}=\frac{9}{4}\)

19 tháng 7 2016

\(\frac{2}{3}.\frac{4}{5}+\frac{1}{3}.\frac{4}{5}=\left(\frac{2}{3}+\frac{1}{3}\right).\frac{4}{5}=1.\frac{4}{5}=\frac{4}{5}\)

\(\frac{1}{2}:\frac{3}{4}+\frac{1}{6}:\frac{3}{4}=\frac{1}{2}.\frac{4}{3}+\frac{1}{6}.\frac{4}{3}=\left(\frac{1}{2}+\frac{1}{6}\right).\frac{4}{3}=\frac{2}{3}.\frac{4}{3}=\frac{8}{9}\)

c,d tương tự 

24 tháng 7 2017

a)2 phần 5

b)4 phần 5

24 tháng 7 2017

\(\frac{2}{3}\times\frac{3}{4}\times\frac{4}{5}=\frac{2}{5}\)

\(\frac{1}{2}:\frac{3}{4}:\frac{5}{6}=\frac{1}{2}\times\frac{4}{3}\times\frac{6}{5}=\frac{1\times2\times2}{5}=\frac{4}{5}\)

6 tháng 4 2018

a)=1/10+1/10+1/10+1/10+1/10+1/10+1/10+1/10+1/10

=1/10*9
=9/10

b)=(3,72+6,28)+(2,05+7,95)

=10+10

=20

11 tháng 4 2017

a) \(\frac{8}{11}-\frac{28}{99}-\frac{14}{99}=\frac{72}{99}-\frac{28}{99}-\frac{14}{99}=\frac{30}{99}=\frac{10}{33}\)

b) \(5\frac{3}{4}-3\frac{1}{2}=\)\(\frac{23}{4}-\frac{7}{2}=\frac{23}{4}-\frac{14}{4}=\frac{9}{4}\)

11 tháng 4 2017

                                                                                                                                                                                                       A) 8/11- 28/99- 14/99                                                                                                                                                                   8/11=72/99                                                                                                                                                                                        (72/99 +28/99)-14/99                                                                                                                                                                          =100/99-14/99                                                                                                                                                                                  =86/99

20 tháng 8 2016

b)\(\left(2016.1017+2017.2018\right).\left(1+\frac{1}{2}:\frac{3}{2}-\frac{4}{3}\right)\)

\(\left(2016.2017+2017.2018\right)\left(1+\frac{1}{3}-\frac{4}{3}\right)\)

\(\left(2016.2017+2017.2018\right).\left(\frac{4}{3}-\frac{4}{3}\right)\)

\(\left(2016.2017+2017.2018\right).0\)

\(=0\)

20 tháng 8 2016

a) \(1001.789+456.128.128-789+912.436\)

\(=\left(1001.789-789\right)+\left(456.2.64.128+912.436\right)\)

\(=789.1000+912.4\left(2048+109\right)\)

\(=789000+912.4.2157\)

\(=8657736\)

19 tháng 4 2015

c) \(\frac{3}{5}+\frac{3}{4}+\frac{2}{5}+\frac{5}{8}+\frac{1}{2}\)

\(\frac{3}{5}+\frac{2}{5}+\left(\frac{6}{8}+\frac{5}{8}+\frac{4}{8}\right)\)

= 1 + \(\frac{15}{8}\)

= 2\(\frac{7}{8}\)

11 tháng 4 2016

3/5+3/4+2/5+5/8+1/2

=(3/5+2/5)+(3/4+1/2)+5/8

=1+5/4+5/8

=1+15/8=23/8

10 tháng 9 2017

2222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222225444444455555555555555555555555555555555555555555555555555555555555555555555555555555555555555555555555555555555

10 tháng 9 2017

\(\frac{4}{18}+\frac{5}{13}+\frac{7}{9}+\frac{21}{13}\)

\(\left(\frac{4}{18}+\frac{7}{9}\right)+\left(\frac{5}{13}+\frac{21}{13}\right)\)

\(1+2\)

\(3\)

\(\frac{4}{3}-\frac{2}{7}-\frac{5}{7}+\frac{2}{3}\)

\(\left(\frac{4}{3}-\frac{2}{3}\right)-\left(\frac{2}{7}+\frac{5}{7}\right)\)

\(\frac{2}{3}-1\)

\(-\frac{1}{3}\)